Camera trapping reveals trends in forest duiker populations in African National Parks. Issue 2 (11th November 2019) - O'Brien, Timothy G.; Ahumada, Jorge; Akampurila, Emmanuel; Beaudrot, Lydia; Boekee, Kelly; Brncic, Terry; Hickey, Jena; Jansen, Patrick A.; Kayijamahe, Charles; Moore, Jennifer; Mugerwa, Badru; Mulindahabi, Felix; et al.
Abstract: Bushmeat hunting is widely cited as cause for declines of wildlife populations throughout Africa. Forest duikers (Bovidae, Cephalophinae) are among the most exploited species. Whether current harvest rates imperil duikers is debated because of the difficulty of accurately assessing population trends. To assess population trends, we first reviewed literature for historical duiker population estimates. Second, we used systematic camera‐trap monitoring to assess population trends for 15 populations of nine duiker species in six national parks in Central and East Africa. We analysed annual monitoring data using Royle‐Nichols heterogeneity‐induced occupancy models to estimate abundance/sample point and derive occupancy estimates. Published density estimates indicate that duiker populations declined significantly throughout Africa between 1973 and 2013. There was a wide range of densities depending on species ( x ¯ range: 0.26–20.6 km −1 ) and whether populations were hunted ( X ¯ =6.3 km −1 ) or unhunted ( X ¯  = 16.3 km −1 ). More recent analysis of camera‐trap monitoring produced different results. Estimated mean point abundance over time was between 0 and 0.99 individuals/point for four populations, between 1.0 and 1.99 for six populations, and greater than 2.0 for five populations. We observed five populations of duikers with negative trends in point abundances, although only one trend was significant and point abundance estimates for three populations were above 2.0 in the final survey year. Six populations showed positive trends in point abundance (three significant), and the remaining populations displayed no trends. Average occupancy was high (Ψ > 0.60) except for three populations. While literature indicates that historical population declines have occurred, most duiker populations appear relatively healthy in monitored parks. Our results indicate that these parks are effective in protecting most duikers despite hunting pressure. We recommend that systematic, standardized camera‐trap monitoring be initiated in other African parks in combination with point‐abundance models to objectively assess forest ungulate population trends. Abstract : We use multi‐year camera trap data and Royle‐Nichols models to evaluate trends in 9 forest duiker species in 6 African parks. We show that, despite hunting pressure, duiker populations are generally healthy in these parks. We argue that systematic camera trap monitoring is an efficient and accurate method to monitor exploited duiker populations.